The Surrendered : Reflections by a Son of Shining Path - Agüero, Jose Carlos (Book collections on Project MUSE., 2021)
"The Surrendered is the English translation of Jose Carlos Agüero acclaimed memoir, his story as the son of two Shining Path militants executed by the Peruvian state. It moves from his parents' political trajectory and life as guerrillas to his own childhood, often spent on the run. The book also examines and contributes to debates about memory and forgiveness, human rights, and reconciliation. In addition to the translation of Agüero s preface and main text, this English edition includes an editors' introduction that explains the hybrid nature of the book and the complex history of the Shining Path. It also contains an extensive interview with Agüero (translated from the Spanish) in which Lazzara and Walker invite him to elaborate on the book's themes and to reflect on its reception and his life as a public intellectual"--